Cellullar Plasticity and Dedifferentiation: A Link Between Cancer Stem Cells, Hypoxia, Cell Injury, and Inflammation - Wijaya, Andi Yasmin (Stem Cell Research and Development Center, Universitas Airlangga, 2018)
Cellular plasticity is the concept of bidirectional dynamics change cells differentiation degree which involved in the regeneration, repair and tissue turnover along the organism livespan. Cellular plasticity and dedifferentiation process are well documented in the discovery of iPCSs by introducing several transcriptional factors known as Yamanaka factor to terminally differentiated somatic cells and reverted into pluripotent state as the ESCs. iPSCs are able to exhibit ESCs differentiation potential which could produce ectodermic, mesodermic, and endodermic cell lineage. In tumour biology, the tumour plasticity also have a similar regulation and play an imporant role for maintaining tumour integrity and survival, particularly in maintaining CSCs population. Various study of cellular plasticity regulation has shown that various factors are involved, in example hypoxia, cell injury, and inflammation. Cells respond to hypoxia, cell injury, and inflammation by chemoattractant which attract repair cells to homing towards injured sites. The homing mechanism of stem cells involved EMT to facilitates migration of stem cells towards injured sites, thus leading to tissue regeneration. On the other hand, cancer metastasis also showed a connection with EMT process. EMT which showed a change in cell properties are linked to dedifferentiation and hypoxia response. Hypoxia condition has been known to preserve and both normal stem cells and CSCs stemness. HIF which protected from degradation in hypoxia condition interact with DNA by binding to HRE. HRE activation trigger transcription of numerous signalling protein which involved in stemness, cell proliferation and survival. Therefore it is concluded that cell injury, hypoxia, and inflammation could programmed cells to undergo dedifferentiation process and involved in EMT regulations. CSCs which resides insides heterogeneous tumour cells population are though to be dynamicly regulate itself in the quietscent and active state through dedifferentiation like the normal stem cells. Understanding how CSCs regulates its active an quietscent state dynamics could provide an important information for novel CSCs targeted therapy development.